Smart system for controlling and monitoring electronic facilities in budget hotel rooms - Daniel Patricko Hutabarat; Robby Saleh; Lukas Sebastian; Jonathan Jonathan; Senanayake Mudiyanselage Namal Arosha (Institute of Advanced Engineering and Science, 2023)
The fundamental attribute of a budget hotel is the provision of essential services at a low cost due to reduced services and facilities. Several services at budget hotels that affect customer choice are related to limitation of accommodation and entertainment services which include the use of television, air conditioning, and other electrical devices. The purpose of this research is to develop a smart system that is used to control and monitor electronic facilities in budget hotel rooms. This system provides budget hotels with the ability to select the electronic facilities that guests want to use in their rooms according to their needs and budget. This system also provides a feature to monitor the use of electronic devices in each room via a web application. The system was developed by using microcontrollers, sensors, radio frequency identification (RFID) devices, a database server, and a web application. The developed system can perfectly provide the room electronic facilities requested by the guest. The system can also monitor the service hour and power consumed by the devices with an accuracy of 99.1% for the service hour and 99.4% for the power consumed.